Candida albicans Hyphal Formation and the Expression of the Efg1-Regulated Proteinases Sap4 to Sap6 Are Required for the Invasion of Parenchymal Organs - Felk, Angelika (American Society for Microbiology, 2002)
The ability to change between yeast and hyphal cells (dimorphism) is known to be a virulence property of the human pathogen Candida albicans. The pathogenesis of disseminated candidosis involves adhesion and penetration of hyphal cells from a colonized mucosal site to internal organs. Parenchymal organs, such as the liver and pancreas, are invaded by C. albicans wild-type hyphal cells between 4 and 24 h after intraperitoneal (i.p.) infection of mice. In contrast, a hypha-deficient mutant lacking the transcription factor Efg1 was not able to invade or damage these organs. To investigate whether this was due to the inability to undergo the dimorphic transition or due to the lack of hypha-associated factors, we investigated the role of secreted aspartic proteinases during tissue invasion and their association with the different morphologies of C. albicans. Wild-type cells expressed a distinct pattern of SAP genes during i.p. infections. Within the first 72 h after infection, SAP1, SAP2, SAP4, SAP5, SAP6, and SAP9 were the most commonly expressed proteinase genes. Sap1 to Sap3 antigens were found on yeast and hyphal cells, while Sap4 to Sap6 antigens were predominantly found on hyphal cells in close contact with host cells, in particular, eosinophilic leukocytes. Mutants lacking EFG1 had either noticeably reduced or higher expressed levels of SAP4 to SAP6 transcripts in vitro depending on the culture conditions. During infection, efg1 mutants had a strongly reduced ability to produce hyphae, which was associated with reduced levels of SAP4 to SAP6 transcripts. Mutants lacking SAP1 to SAP3 had invasive properties indistinguishable from those of wild-type cells. In contrast, a triple mutant lacking SAP4 to SAP6 showed strongly reduced invasiveness but still produced hyphal cells. When the tissue damage of liver and pancreas caused by single sap4, sap5, and sap6 and double sap4 and -6, sap5 and -6, and sap4 and -5 double mutants was compared to the damage caused by wild-type cells, all mutants which lacked functional SAP6 showed significantly reduced tissue damage. These data demonstrate that strains which produce hyphal cells but lack hypha-associated proteinases, particularly that encoded by SAP6, are less invasive. In addition, it can be concluded that the reduced virulence of hypha-deficient mutants is not only due to the inability to form hyphae but also due to modified expression of the SAP genes normally associated with the hyphal morphology.